2015
DOI: 10.1007/s13149-015-0419-4
|View full text |Cite
|
Sign up to set email alerts
|

Analyses des réponses IgG dirigées contre des antigènes candidats vaccins dans le paludisme urbain non aggravé à Dakar (Sénégal) : variations suivant l’âge et les densités parasitaires

Abstract: Malaria remains a major problem in African countries despite substantial decreases in morbidity and mortality due to sustained control programs. Studies for the evaluation of qualitative or quantitative Ab responses to key targets of anti-plasmodium immunity were mostly done in rural endemic setting compared to urban area. In a cohort of 200 patients with mild malaria and living in Dakar, we analyze total and subclasses IgG responses to a panel of P. falciparum blood stage antigens: MSP1p19, MSP3, EB200, GST-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In our study, these associations were not observed. Discordances can be explained firstly by the low endemicity in urban area of Dakar 17 and the second explanation can be the fact that our study population was constituted by symptomatic malaria patients and as described previously no significant difference of IgG anti‐ P. falciparum levels were reported between adults and children hospitalized patients 26, 27.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, these associations were not observed. Discordances can be explained firstly by the low endemicity in urban area of Dakar 17 and the second explanation can be the fact that our study population was constituted by symptomatic malaria patients and as described previously no significant difference of IgG anti‐ P. falciparum levels were reported between adults and children hospitalized patients 26, 27.…”
Section: Discussionmentioning
confidence: 61%
“…Discrepancies were especially apparent when analysing antibody responses in CM samples. The profile of antibody responses for low endemic urban malaria was substantially different, with no relationship between age and response level as already observed in this setting [ 45 ]. Such profiles reflect the limited cumulative individual exposition in urban areas, in agreement with the observed antigen dependent longevity of antibody responses which is independent of response magnitude [ 46 ].…”
Section: Discussionmentioning
confidence: 61%
“…The flow cytometry technique has been already used as a relevant surrogate marker in IgG binding to iRBC in different contexts: before and after vaccination trials [ 18 ], as function of age and hemoglobin type in Malian children [ 38 ] and as a differential marker in Senegalese individuals living in rural settings with different levels of endemicity [ 17 ]. In urban setting, previous studies focused on relationship between antibody responses to defined antigens and clinicoepidemiology such as age of individuals and severity of outcome [ 23 , 33 ]. However, as reported in rural symptomatic malaria, the amount of sequestered parasites increased with disease severity [ 7 ], and the binding of P. falciparum -infected RBCs to microvascular endothelial cells induces pathological sequelae in microvessels that are associated with the symptoms and severe manifestations such as CM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It expresses the C-proximal region of Pf EMP3, a high-molecular weight host membrane-associated protein [ 31 , 32 ]. The control protein was the GST carrier previously reported [ 23 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation